2014
DOI: 10.1007/s12032-014-0942-3
|View full text |Cite
|
Sign up to set email alerts
|

No association between XRCC3 Thr241Met and XPD Lys751Gln polymorphisms and the risk of colorectal cancer in West Algerian population: a case–control study

Abstract: Colorectal cancer (CRC) is a complex and multifactorial disease, in which genetic and environmental factors both seem to play a part. Many epidemiological studies have explored the association between genetic polymorphisms of X-ray repair cross-complementing group 3 (XRCC3) (Thr241Met) and Xeroderma pigmentosum group D (XPD) lysine to glutamine at codon 751 (Lys751Gln) and risk of CRC in various populations; however, the results are controversial. We conducted this case-control study in a West Algerian populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…90 From Indian subcontinent, two populations practicing consanguineous marriages reported an association with increased risk, for colorectal cancer in Kashmiri population 50 and breast cancer in Pakistani population. 91 For XRCC3 p.Thr241Met polymorphism, no association was reported with gastric cancer in Italian population 92 and with colorectal cancer in the West Algerian population 93 but an association with an increased risk was reported for lung cancer in an Italian population, 23 oral SCC in Thai population, 94 and gastric cancer in the Chinese population. 95 On the other hand, a protective role of CT and TT genotype has been reported in colorectal cancer in Polish population 96 and Basal cell carcinoma of the skin in population from Hungary, Romania and Slovakia.…”
Section: Discussionmentioning
confidence: 99%
“…90 From Indian subcontinent, two populations practicing consanguineous marriages reported an association with increased risk, for colorectal cancer in Kashmiri population 50 and breast cancer in Pakistani population. 91 For XRCC3 p.Thr241Met polymorphism, no association was reported with gastric cancer in Italian population 92 and with colorectal cancer in the West Algerian population 93 but an association with an increased risk was reported for lung cancer in an Italian population, 23 oral SCC in Thai population, 94 and gastric cancer in the Chinese population. 95 On the other hand, a protective role of CT and TT genotype has been reported in colorectal cancer in Polish population 96 and Basal cell carcinoma of the skin in population from Hungary, Romania and Slovakia.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis results showed that the XRCC3 T241M polymorphism was not associated with CRC risk both in Asians and in Caucasians. There was only one study of Africans, and thus further studies examining Africans should be conducted (Moghtit et al, 2014). Stratification by sample size (> 500) for subgroup analysis revealed no significant association, indicating there was no smallstudy bias in our meta-analysis.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, numerous studies have examined the association between the XRCC3 T241M polymorphism and CRC. However, the results are inconsistent, likely because these studies were single case-control studies including small sample sizes (Moghtit et al, 2014). To clarify these inconsistent findings, we conducted this meta-analysis to obtain more reliable results by combining a larger number eligible studies, increasing the sample size, and conducting subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations